Deaboriginization of Russian Sociological Expertise Industry: Dispute vs. Conquista - Roman, Bumagin (Journal of Economic Sociology, 2019)
The article is a rejoinder to Nikolai Babich’s polemical response to our paper “Criticism of the survey approach for analyzing the mutual similarity in the appearance of consumer products within one product category”, published in the Journal of Economic Sociology (2018, vol. 19, no 2, pp. 86–117). Babich named his article “Methodological Reflection in a Pith Helmet” (Journal of Economic Sociology 2019, vol. 20, no 1, pp. 188–196) having thus drawn analogy between scientific criticism and colonial approach that white European colonialists practiced towards the aboriginal population of overseas territories and towards their social institutions. Our replica disputes the validity of using the “Aboriginal” label to the current state of the industry of sociological expertise in Russia as well as the validity of using the complementary term “Colonialist” to designate the colleagues trying to criticize the established research and discursive practices. We also point on the need for more active use of theoretical baggage of classical and modern sociology and sociology of language in the study of visual signs, call for the intensification of scientific dispute based on Mertonian organized skepticism. We develop our criticism in two planes. On the one hand, an attempt is made to deconstruct the colonialist argument as a special case of ad hominem arguments prohibited in the scientific debate. On the other hand, through the prism of these arguments, we once again reconstruct the logic of our approach to the study of similarities and differences in the appearance of FMCG products, based on proven and/or conventional positions of sociological science and sociology of language.